NUTRIŢIE - Magdalena Mititelu; Marius Sorinel Neacşu; Corina-Bianca Ioniţă-Mîndrican; Menadoru Coza; Mirela Şeşureac; Mădălina Cartojan; Daniela Holingher; Gabriel Olteanu (Farmacist.ro)
Apa, componentă indispensabilă pentru sănătatea şi funcţionarea organismului uman